Classroom Questions Used by History Teachers and the Way of Directing Them and Dealing with Students Answers - al-khatatenh, Thekrayat mohmmad jebril (Journal of Educational and Psychological Sciences, 2021)
This study aimed at investigating the levels of classroom questions most commonly used among, The quasi-experimental method was used in the study to test the program. To achieve the goal of this study a note-taking card was designed and was formed of three parts: questions according to the revised version of blooms taxonomy, skills of directing questions and the skills of how to deal with students answers. Both reliability and validity of the instrument were checked. The not taking card was distributed on (38) both male and female teachers those who teach History in AL-Karak District in Jordan and that was by observing to situations for each teacher. The results showed that the most level that was commonly used by teachers was remembering obtained (0.38%) and memorizing obtained (0.36%) and understanding obtained (0.03%)and the least commonly used was evaluative obtained (0.05%) and creative questions. There were statistically significant obtained (0.25%) differences due to experience obtained (0.04%) teachers with (11 years of experience and more) focus on informative questions. As for the teachers with (1-5)years of experience and from (6-10) years focus on the questions that measure higher levels like such as evaluation, analyses and composition. Based on results the researcher provided a set of recommendations such as improving the quality questions focus on higher levels of thinking, teachers training in the Directorate of Education in karak, all over the kingdom of Jordan.